555 Design, development, and implementation of an investigator-focused CRM platform for managing navigation, consults, services, and delivery - Brian Sevier; Kacey L. Richards; Erica Rocco; Christine Chaisson (Journal of Clinical and Translational Science)
Objectives/Goals: Our goal is to develop a CRM platform to streamline support for investigators, optimize resource use, and enhance service delivery within a CTSA institution. This platform will measure outcomes, improve transparency, and ensure compliance, creating an efficient, supportive research environment. Methods/Study Population: Beginning with the design concepts and collecting technical requirements, ensuring alignment with the needs of investigators, administrators, and service units. Apply project management methodologies to iteratively design, prototype, and test features. Focus on user-centric interfaces and seamless integration with institutional systems. Incorporate stringent data security protocols in compliance with regulatory standards. Conduct pilot studies to refine functionalities and gather constructive feedback. Facilitate extensive user training programs and offer continuous support. Regularly monitor performance metrics, iterating based on empirical data and user feedback to ensure continuous enhancement and adherence to institutional objectives. Results/Anticipated Results: YCCI successfully designed, developed, and implemented a CRM platform for managing the intake, navigation, consultation, service delivery, and outcomes tracking of the clinical and translational science activities that are supported by and beyond the CTSA-supported infrastructure. The CRM platform has been live in production since roughly July 1, 2024, and YCCI is excited to share data, results, and outcomes with the ACTS community. Discussion/Significance of Impact: YCCI’s CRM platform advances the CTS mission by streamlining PI support, enhancing resource utilization, and fostering inter-team collaboration within the research ops and administration teams. Measuring outcomes and service efficiency enables data-driven decisions, ensuring continuous improvement, and impactful translational science.